Trademark Dispute Between Starbucks Corporation and Sumatera Tobacco Trading Company: An Analysis of the Supreme Court Decision No. 836 K/PDT.SUS-HKI/2022 - Adenfa, Alexandrio; Rasji, Rasji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research analyzes the application of good faith principle in trademark registration, particularly in the trademark dispute between Starbucks Corporation and PT. Sumatera Tobacco Trading Company decided by Supreme Court Decision No. 836 K/PDT.SUS-HKI/2022. The research aims to analyze the implementation of good faith principle in well-known trademark registration under Law No. 20 of 2016 and evaluate the Supreme Court's legal considerations in protecting well-known trademarks. This normative legal research uses statutory and case analysis approaches, with primary legal sources (laws and court decisions) and secondary sources (books, journals, legal articles). Data analysis is conducted descriptively with inductive conclusions. Results show that the Supreme Court successfully applied the good faith principle by canceling the